Answer:
![x=-(3)/(5)](https://img.qammunity.org/2020/formulas/mathematics/high-school/1m96gi8uol5uy0tg7xs5s44282t7mtpe9x.png)
Explanation:
By the negative exponent rule, you have that:
![((1)/(a))^n=a^(-n)](https://img.qammunity.org/2020/formulas/mathematics/high-school/wybo84ihxu6fclrnm0k4erx4f7d5cjtzg6.png)
By the exponents properties, you know that:
![(m^n)^l=m^((nl))](https://img.qammunity.org/2020/formulas/mathematics/high-school/d2gz0fpbml3sogdrjpv4ve7cd4qmvhsmew.png)
You can rewrite 16 and 9 as following:
16=4²
9=3²
Therefore, you can rewrite the left side of the equation has following:
![((4^2)/(3^2))^((2x+5))=((3)/(4))^((x-7))\\\\((3^2)/(4^2))^(-(2x+5))=((3)/(4))^((x-7))\\\\((3)/(4))^(-2(2x+5))=((3)/(4))^((x-7))](https://img.qammunity.org/2020/formulas/mathematics/high-school/7agzfymtogmpsaqdibn6d1zah7ygix4b1l.png)
As the base are equal, then:
![-2(2x+5)=x-7](https://img.qammunity.org/2020/formulas/mathematics/high-school/a5bhpc5jf91hwroi8y5a5x4ykxin9l4b0q.png)
Solve for x:
![-2(2x+5)=x-7\\-4x-10=x-7\\-4x-x=-7+10\\-5x=3\\x=-(3)/(5)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ayzg3opk70tuhy3vamx8ymsv50p544hlqy.png)